Low-temperature magnetic behavior of the organic-based magnet Na[FeO6(C10H6N)3] - Dyakonov, V.P.; Zubov, E.; Aksimentyeva, E.; Dyakonov, K.; Piechota, S.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The static and dynamic aspects of magnetic behavior of the complex of iron with 1-nitroso-2-naphthol Na[FeO6(C10H6N)3] as a function of temperature, frequency and magnetic field have been analysed. The ac susceptibility (cac) and dc magnetization (Mdc) were measured over a temperature range of 1.5–200 K in external magnetic field up to 90 kOe and over a frequency range of 95–2000 Hz. The experimental data indicate the absence of magnetic long range order in this complex. The magnetization does not reach a saturation in field of 90 kOe at 1.5 K. At low temperatures, the following characteristic peculiarities of magnetic behavior of complex studied have been found, namely : cusp-like anomalies in the ac susceptibility and zero field coold (ZFC) magnetization at Tcusp = 17 K; frequency dependence of the Tcusp temperature; remanence and time-dependent relaxation of ZFC magnetization. Attempts were made to compare the cac and Mdc anomalies in complex studied with those of other magnetic systems. Comparison of characteristic peculiarities of magnetic behavior of the spin-glasses and superparamagnets was also performed. Although superparamagnetic behavior should not be completely ruled out as an explanation of the freezing phenomena in sample studied, the analysis of experimental results strongly suggests that the spin-glass-like behavior is a more consistent explanation.